Clinical outcomes among low‐titer group O whole blood recipients compared to recipients of conventional components in civilian trauma resuscitation. Issue 8 (30th August 2018) - Seheult, Jansen N.; Anto, Vincent; Alarcon, Louis H.; Sperry, Jason L.; Triulzi, Darrell J.; Yazer, Mark H.
Abstract : BACKGROUND: The serological safety of transfusing ≤4 units of low titer group O whole blood (LTOWB) in civilian trauma patients has been demonstrated. This study investigated clinical outcomes of LTOWB recipients compared to patients who received only conventional blood components during their resuscitation. STUDY DESIGN AND METHODS: A retrospective analysis of trauma patients' medical records who received LTOWB during the first 24 hours of their admission was performed. Using a 12‐parameter propensity matching strategy, LTOWB recipients were matched to other patients who received at least one red blood cell (RBC) unit during their first 24 hours of admission but not LTOWB. The primary outcomes were mortality and blood use. RESULTS: A total of 135 patients who received LTOWB (median 2 units) were matched to 135 patients who received conventional components. There were no significant differences in the matching parameters between the groups. There were no significant differences in outcomes between the conventional component and LTOWB groups: median (interquartile range) in‐hospital mortality, 24.4% vs. 18.5% (respectively, p = 0.24); 24‐hour mortality, 12.6% vs. 8.9% (respectively, p = 0.33). The hospital and intensive care unit lengths of stay were not significantly different between groups. The median number of RBC units transfused, including the contribution from the LTOWB, was not significantly different between the groups. The time to normalization of elevated plasma lactate levels tended to be shorter among the LTOWB recipients compared to the conventional component recipients (median 8.1 [3.7‐15.4] hr vs. 13.2 [4.4‐26.8] hr, respectively, p = 0.05). CONCLUSION: The LTOWB recipients had similar clinical outcomes compared to recipients of conventional component therapy.